The impact of responsible gambling framing on people with lived experience of gambling harm - Marko, Sarah; Thomas, Samantha L.; Pitt, Hannah; Daube, Mike (Frontiers in Sociology, 2023)
Background The framing of health issues influences how people think about and respond to these topics. Gambling has largely been framed as an issue of personal responsibility, with the gambling industry, governments and some researchers promoting responsible gambling strategies as a way to address gambling harm. While there is evidence that the internalization of personal responsibility can negatively impact gamblers, this study aimed to explore how people who have experienced gambling harm interpret and apply personal responsibility frames and ‘gamble responsibly' messages in their lives. Methods In-depth semi-structured interviews were conducted via Zoom and telephone with 15 gamblers who had been harmed by their own gambling and six affected others who had been harmed by someone else's gambling. This study was informed by public health and critical qualitative approaches to inquiry. The data were analyzed using reflexive thematic analysis. Results Four themes were constructed from the data. First, gamblers and affected others generally conceptualized gambling and gambling harm as being the responsibility of the individual because it was perceived as the outcome of individual behavior. Second, they attempted to apply responsibility to their own experience either as gamblers who tried to stop or reduce their gambling, or affected others who felt responsible for helping the gambler in their lives. Third, gamblers and affected others were negatively impacted when it was perceived the gambler could not ‘control' their gambling or had not done enough to take responsibility. Finally, gamblers and affected others recommended responsible gambling strategies be reframed to be more effective at addressing gambling harm. Conclusion This study provides evidence further supporting research demonstrating that personal responsibility frames may have unintended or negative consequences for gamblers and affected others. It underscores the need to reframe public messages about gambling away from responsible gambling, and toward research-based messages that can complement broader legislative changes and other measures to protect individuals.